2021
DOI: 10.1186/s42466-021-00111-6
|View full text |Cite
|
Sign up to set email alerts
|

COX2 expression is associated with preoperative tumor volume but not with volumetric tumor growth in vestibular schwannoma

Abstract: Objective Vestibular schwannomas (VS) are benign slow growing tumors arising from the vestibular nerve. The role of cyclooxygenase 2 (COX2) in tumor development of growth has been addressed in a few studies with contradictory results and suggestions. We recently analyzed the immunohistochemical expression of COX2 in 1044 VS samples and described an association of higher COX2 expression with proliferation but found no influence by regular intake of acetylsalicylic acid. We now collected volumetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In addition, a positive correlation between COX2 expression and tumor extension (Hannover classification) in 1048 VS was detected by IHC [ 19 ]. However, no increase in COX2 expression was found with an increasing volumetric growth rate [ 25 ]. Treatment with COX2 inhibitors did not affect COX2 expression and VS- growth [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a positive correlation between COX2 expression and tumor extension (Hannover classification) in 1048 VS was detected by IHC [ 19 ]. However, no increase in COX2 expression was found with an increasing volumetric growth rate [ 25 ]. Treatment with COX2 inhibitors did not affect COX2 expression and VS- growth [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Koutsimpelas et al examined a positive correlation between proliferation index and tumor diameter in 182 sporadic VS [ 18 ]. In contrast to this, analysis of 747 VS showed increasing Ki-67 expression in smaller tumors and VS with a higher growth rate [ 25 ]. In contrast to the previous study, our study showed lower expression of Ki-67 in large VS and in fast-growing VS. Abundant Ki-67 expression was also detected in the IHC sections of the smaller VS.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the series of our department with 1381 vestibular schwannomas included only 202 patients of that age category (14.6%). We recently showed in a retrospective analysis that younger patients, suffering from sporadic VS, had larger tumor volumes and higher volumetric tumor growth rates prior to surgery [ 45 ] suggesting that sporadic VS developing at a younger age may behave differently. Furthermore, a more cautious indication for radiosurgery for vestibular schwannomas in NF2 patients has already been suggested [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is based on an inflammatory component being predominant in growing VS. Leisz et al reported interesting results in their cohort, demonstrating a positive correlation between macrophage marker (CD68 and CD163) expression and VS volume and growth rate [11]. However, COX2, Ki-67, and VEGF expression were all negatively correlated with large VS and fastgrowing tumors, contradicting previous studies [12,13]. One explanation is an increased recruitment of M2 macrophages in active, growing VS, leading to swelling and escalating growth [14].…”
mentioning
confidence: 87%